2022
DOI: 10.1155/2022/1505040
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Analysis of the Effectiveness of International Law in Global Environmental Relations from the Perspective of International Institutional Theory

Abstract: Since the 1970s, mankind has become increasingly sensitive to major world environmental protection issues, and the globalenvironmental protection laws and regulations system formed to deal with suchspecific issues has rapidly expanded in scope and depth. From the initial environmental issues in the study of international relations theory to the development of environmental issues in the study of global governance, and then the concept of global environmental governance came out and developed rapidly. This tren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…However, resilience theory faces challenges such as trade-offs between resilience and efficiency, scale dependence, and the constant presence of unpredictable situations that require thoughtful action plans. Overall, resilience theory offers a multidisciplinary approach to understanding and managing systems' resilience and resilience (Yu 2022). Resilience theory is a crucial tool for managing the complexity of dynamic systems, emphasizing the importance of enduring shocks and flourishing in uncertainty.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…However, resilience theory faces challenges such as trade-offs between resilience and efficiency, scale dependence, and the constant presence of unpredictable situations that require thoughtful action plans. Overall, resilience theory offers a multidisciplinary approach to understanding and managing systems' resilience and resilience (Yu 2022). Resilience theory is a crucial tool for managing the complexity of dynamic systems, emphasizing the importance of enduring shocks and flourishing in uncertainty.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…International governance regimes and institutions play an important role in addressing global environmental threats to natural ecosystems, such as climate change and the global biodiversity decline, by providing binding rules and standards, priorities and targets, technical reports and guidelines and a forum for collaborative decision-making, sharing expertise and highlighting best practices (Techera and Klein, 2014;Richardson, 2016;Yu, 2022). For ecosystems, there is no single regime of relevance and instead the governance landscape is comprised of multiple legal instruments, institutions, and programmes.…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%